NextGenGuides: AI-Enhanced Multimedia Navigation and Content Creation for Cultural Heritage - Amendola, Danilo; Rodríguez Reiners, Luis Ángel; Alviano, Mario (Street Art & Urban Creativity, 2025)
Cultural heritage digitalization still faces challenges in scalable content creation, seamless indoor/outdoor navigation, and accessibility. NextGenGuides is an integrated multimedia platform combining AI-assisted content generation, precise 3D geo-localization, and sensory guidance for visually impaired users. Its human–AI collaborative framework ensures authentic, high-quality narratives, while a modular cloud architecture supports scalability and inclusion. The platform provides a holistic and sustainable solution for digital tourism and cultural heritage valorization.